2015
DOI: 10.1039/c4cp05521g
|View full text |Cite
|
Sign up to set email alerts
|

Properties and photochemistry of valence-induced-Ti3+enriched (Nb,N)-codoped anatase TiO2semiconductors

Abstract: Nb and N codoped TiO2s are outstandingly versatile semiconductor oxides. Their high conductivity makes them valid alternatives to commercially available, but very expensive, conductive oxides. They show increased photonic efficiencies compared to the cases of solely Nb or N doped TiO2, when used as visible light sensitised photocatalysts. Furthermore, they are excellent materials for O2 sensors at very low temperature. Despite these remarkable properties, a clear picture of the electronic and optical mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
(81 reference statements)
3
13
0
Order By: Relevance
“…These spectral changes match what has been previously reported for similar Ndoped TiO 2 samples. 37,40,42,43,46 The EPR spectrum recorded under light irradiation is also reported in the SI at higher resolution with overall simulation; deconvolution of the N1, N2…”
Section: Photochemical Responsementioning
confidence: 98%
“…These spectral changes match what has been previously reported for similar Ndoped TiO 2 samples. 37,40,42,43,46 The EPR spectrum recorded under light irradiation is also reported in the SI at higher resolution with overall simulation; deconvolution of the N1, N2…”
Section: Photochemical Responsementioning
confidence: 98%
“…The higher loading of dye and greater interaction between dye and TiO 2 , potentially enhance electron injection which along with reduced electron recombination leads to better photovoltaic performances. Again, from Taucs’ plot (Figure b) it was observed that the lower the particle size of the material, higher is the band‐gap energy of the material and materials with higher band gap energy have better photovoltaic profiles ,. Interestingly, TNP‐II, with the highest band gap, exhibited the best energy conversion efficiency.…”
Section: Resultsmentioning
confidence: 95%
“…Again, from Taucs' plot ( Figure 2b) it was observed that the lower the particle size of the material, higher is the band-gap energy of the material and materials with higher band gap energy have better photovoltaic profiles. [53,54] Interestingly, TNP-II, with the highest band gap, exhibited the best energy conversion efficiency.…”
Section: Mott -Schottky Plot and Flat Band Potentialmentioning
confidence: 99%
“…where C SC is the capacitance of the space charge region, ϵ 0 is the permittivity of free space, q is the electronic charge, ϵ is the dielectric constant of the semiconductor (taken as 41 for anatase TiO 2 ), E is the applied potential, E fb is the flat band potential and N D is the donor density. The flat band potentials were determined by the extrapolation of fitting linear region of the Mott‐Schottky plot.…”
Section: Resultsmentioning
confidence: 99%